Optimization of Microelectrolysis Treatment to Remove Arsenic from Landfill Gas Condensate and Correlations between Changes of Redox Potential and Arsenic Removal - Pinochet Troncoso, Ivette Andrea Del Carmen (My University, 2023)
This thesis is focused on the optimization of the microelectrolysis (ME) process for removing arsenic from landfill gas (LFG) condensate. The ME process utilizes redox and adsorption processes that take place at the interface of zero-valent iron and activated carbon. Multiple optimization experiments were conducted in this study to minimize treatment time and resources while maximizing arsenic removal. The study found that minimizing the ingress of atmospheric oxygen to the reactor, and that using mechanical mixing in a batch conical bottom reactor is the optimal configuration for the treatment. The results also showed that granular activated carbon (GAC) and zero valent iron (ZVI) are highly effective at removing arsenic from the LFG condensate when used in sufficiently high dosages. Multiple batches of LFG condensate can be treated using the same amount of the combined ZVI/GAC active media. Additionally, the study found that a more acidic environment (e.g., pH 3) can enhance the efficiency of contaminant removal, and that a treatment duration of 30 minutes is typically sufficient to achieve >90% As removal. Results of this study suggest that future research should further explore a detailed correlation between the redox potential measured in the ME reactors and the As removal efficiency. It is also necessary to find the optimal mixing parameters to achieve a good balance of both active media particle suspension in the reactor and catalytic interactions between ZVI and GAC, and to determine the maximum number of solid reuse cycles that ZVI and GAC can withstand.
Thesis (Master's)--University of Washington, 2023
Keywords: Arsenic; Landfill gas condensate; Microelectrolysis; Reactor; Redox; Removal; Environmental engineering; Civil engineering